Language, Power, and the Economics of Education in Morocco - Errihani, Mohammed (Cham : Springer International Publishing : Imprint: Springer, 2023)
This volume provides a comprehensive understanding and assessment of language policy in education in Morocco. All aspects related to language policy and the effect on the education sector for more than half a century in Morocco are included in the book. The book traces the role that the linguistic medium has played in the educational system in Morocco since its independence from the French in 1956. It examines the role that various language policies have played in the educational sector and provides an in-depth analysis of the most recent language policy recognizing Berber, making it an official language and a mandatory subject in all schools. As such, this book is on the cutting edge of language policy as it also examines a policy that is still being rolled out. It also addresses the role of political pressure, and social and political conflict on language policy in Morocco, and how the linguistic medium has failed to guarantee the basic goals of equity, equality and social justice that assure a decent future for every citizen.
Introduction -- First, it was Arabization... -- An Educational Crisis: Is Language to Blame? -- Language Reform(s) -- The Mother Tongue Debate -- Democratizing Education: English as a Medium of Instruction? -- A Saturated Linguistic Scene: Should my Child be Required to Learn Berber too? -- Education and Social Justice: Entrenched Inequality and lack of Equity.-The Language Problem next door: Language-in-education Policies in Algeria -- Conclusion. .
Keywords: Education and state; Language policy; Anthropological linguistics; Educational Policy and Politics; Language Policy and Planning; Linguistic Anthropology